Sequence Alignment - Erciyes, Kayhan (Distributed and Sequential Algorithms for Bioinformatics, 2015)
Sequence alignment is the basic and most widely used method of comparing two or more biological sequences. It can be used as the first step of various sequence analysis tasks to quantify the similarities between the sequences. The goal of sequence alignment is to transform one sequence to another with minimum number of modifications. It can be performed in polynomial time between two sequences but heuristics are commonly used to compare multiple sequences. Global alignment is the process of comparing two or more sequences as a whole and is commonly used for homologous sequences. On the other hand, local alignment aims to find similar subsequences between two or more inputs which may be very diverse when considered as a whole. Pairwise alignment algorithms input two sequences and multiple alignment methods work on a set of sequences. In this chapter; we describe algorithms, methods, and tools for these different forms of sequence alignment starting with sequential algorithms and then we detail distributed versions of these algorithms.